Imaging Findings in Schwannomas of the Jugular Foramen - Eldevik, O. Petter (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Tumors of the cranial nerve sheath constitute 5% to 10% of all intracranial neoplasms, yet few articles have described their CT and MR characteristics. We report the imaging findings in a relatively large series of schwannomas of the jugular foramen, contrasting them with other disease entities, especially vestibular schwannomas and tumors of the glomus jugulare. METHODS: CT and/or MR studies of eight patients who underwent surgery for histologically proved schwannomas were reviewed retrospectively. One additional patient with an assumed schwannoma of the jugular foramen, who did not have surgery, was also included. RESULTS: Surgical findings showed schwannomas of the glossopharyngeal nerve in seven patients and tumor involvement of both the glossopharyngeal and vagal nerves in one patient. All tumors were partially located within the jugular foramen. Growth extending within the temporal bone was typical. Tumor extended into the posterior cranial fossa in all nine patients and produced mass effect on the brain stem and/or cerebellum in seven patients; in five patients, tumor extended below the skull base. On unenhanced CT scans, tumors were isodense with brain in six patients and hypodense in two. In seven patients, CT scans with bone algorithm showed an enlarged jugular foramen with sharply rounded bone borders and a sclerotic rim. On MR images, T1 signal from tumor was low and T2 signal was high relative to white matter in all patients. Contrast enhancement on CT and/or MR studies was strong in eight patients and moderate in one. CONCLUSION: Schwannoma of the jugular foramen is characteristically a sharply demarcated, contrast-enhancing tumor, typically centered on or based in an enlarged jugular foramen with sharply rounded bone borders and a sclerotic rim. Intraosseous extension may be marked.